Managing Eutrophication in the Szczecin (Oder) Lagoon-Development, Present State and Future Perspectives - Friedland, René; Schernewski, Gerald; Gräwe, Ulf; Greipsland, Inga; Palazzo, Dalila; Pastuszak, Marianna (Frontiers in Marine Science, 2019)
High riverine nutrient loads caused poor water quality, low water transparency and an unsatisfactory ecological status in the Szczecin (Oder) Lagoon, a trans-boundary water at the southern shore of the Baltic Sea. Total annual riverine N (P) loads into the lagoon raised at the 20th century from approx. 14,000~t~TN (1,000~t~TP) to 115,000~t~TN (10,500~t~TP) in the 1980ties and declined to about 56,750~t~TN (2,800~t~TP) after 2010. Nutrient concentrations, water transparency (Secchi depth) and chlorophyll-a showed a positive response to the reduced nutrient loads in the Polish eastern lagoon. This was not the case in the German western lagoon, where summer Secchi depth is 0.6 m and mean chlorophyll-a concentration is four times above the threshold for the Good Ecological Status. Measures to improve the water quality focused until now purely on nutrient load reductions, but the nutrient load targets and Maximal Allowable Inputs are contradicting between EU Water Framework Directive and EU Marine Strategy Framework Directive. According to the HELCOM Baltic Sea Action Plan, the thresholds of the annual riverine nutrient inputs to the lagoon would be about 48,850~t~N (1,570~t~P). Actions in the river basins that would allow meeting these targets are hardly achievable. Even if the load targets would be fully implemented, they are not sufficient to transfer the lagoon into a non-eutrophic state. The implementation of EU Water Framework Directive is further hampered, as consistent water quality thresholds for the two parts of Szczecin Lagoon are missing. An approach to harmonize them is presented, which incorporates the spatial differences. By implementing consistent water quality targets, Szczecin Lagoon could serve as blueprint for other trans-boundary waters. In the western lagoon, nutrient load reductions in the past decades had no effect on the water quality. High water residence times, frequent sediment resuspension and the missing submerged vegetation inhibit the load reduction effects on the water quality. Internal measures in the western lagoon are necessary, which aim at removing nutrients and$\/$ or increasing water transparency to overcome the hysteresis effect and to initiate a recovery of macrophytes. The most promising approach seems the cultivation of zebra mussels.